Atypical mycobacterial infection in post laparoscopy surgical wounds: our observations and review of literature - Krishnappa, Rohit; Samarasam, Inian (International Surgery Journal, 2017)
Background: Nontuberculous mycobacteria (NTM) are a rare cause of chronic surgical infection in humans. These infections are commonly seen in the setting of laparoscopic surgery, due to poor sterilization techniques. This case series analyses the clinical features and management of patients with biopsy proven NTM infection, with a review of the current literature. Methods: Patients with chronic surgical site infections admitted to our surgical unit, over a 5-year period from January 2008 to December 2012 were analyzed in this study. A total of 24 patients with biopsy proven NTM were included. The clinical details, management protocol is discussed. Results: A total of 24 patients were analysed. Most of our patients were females (n=16) and this infection was most commonly seen following laparoscopic cholecystectomy (n=10). The symptoms were usually benign but persistent watery or purulent discharge. Mycobacterium fortuitum and Mycobacterium chelonae were the predominant organisms isolated. All patients in this series were treated with extensive surgical debridement and long-term antibiotics. A multidrug antibiotic regimen consisting of Ciprofloxacin, Clarithromycin and Amikacin was used. All of our patients showed good response to treatment during stay and recurrence was seen in 3 patients who had delayed healing wounds. Conclusions: NTM is not an uncommon infection and can occur following laparoscopic or open surgical procedures. Improper sterilization and reuse of laparoscopic or open instruments accounts for the majority of the cases. When laparoscopic instruments are reused, following strict sterilization protocols is necessary to prevent this infection. When established, this infection should be treated aggressively with adequate surgical debridement, followed by long term antibiotics.